Multigrip Flexible Device: Electromyographical Analysis and Comparison With the Bench Press Exercise - Giorgio, Pierre; Samozino, Pierre; Morin, Jean-Benoît (Journal of strength and conditioning research, 2009)
Giorgio, P, Samozino, P, and Morin, JB. Multigrip flexible deviceelectromyographical analysis and comparison with the bench press exercise. J Strength Cond Res 23(2)652-659, 2009-The aim of this study was to analyze a multigrip warpable fitness device that opposes elastic-like resistance when subjects aim at either compressing or stretching it out of its initial shape, and to compare the electromyographical (EMG) activity of the pectoralis major, anterior deltoid, and triceps brachii induced by various exercises performed using this device with that induced by bench press exercises at different loading levels. Peak EMG activity was measured in 13 healthy physical education students for concentric 2-second phases during bench press exercises at 20, 40, 60, 80, and 100% of maximal repetition, and for 6 movements with the device tested (4 different grips, 3 arms positions, both in concentric and isometric conditions). The main results show that the muscle solicitation that could be reached was significantly different depending on the grip used (p < 0.05) and was equivalent to that observed in bench press exercises performed against loads ranging from 20 to 80% of the maximal repetition. Changing arm position (from the standard position of use to outstretched arms or a butterfly-like position) resulted in significantly increasing levels of activation for the pectoralis major and the anterior deltoid. The instability phenomena observed when performing isometric actions with this device did not result in higher levels of activation, which does not allow us to classify it among instability devices (such as wobble boards or balls). It seems from our results that this device is worth considering for both warm-up and strengthening matters and in the field of physical therapy and rehabilitation, allowing, for instance, progressive force production in upper-limb joint strengthening processes.